Financial Literacy of Elementary Students: A Preliminary Study on Early Financial Knowledge and Attitudes in Jakarta and Bekasi - Mukhlis, Septian; Kurnia, Ira Restu; Syahwildan, Muhamad; Sulistiawati, Nika; Kenju, Rifa Naila Meiliani Manoppo (International Journal of Education and Learning Studies, 2025)
This study aims to analyze the financial literacy of elementary school students through three dimensions: knowledge, attitudes, and financial behavior. Using a descriptive-quantitative design supported by qualitative data, the study involved 240 fifth- and sixth-grade students from elementary schools in Bekasi and Jakarta. The instrument was a 25-item financial literacy questionnaire on a Likert scale, analyzed using descriptive statistics, complemented by observations and informal interviews. The findings show that 62.1% of students fall into the low category of financial knowledge, while only 19.5% achieve a high level. Financial attitudes tend to be consumptive (M=3.89; SD=0.72), and financial behavior has not yet developed consistently, with only 27.8% of students practicing regular saving. The main inhibiting factors are the limited integration of financial education in the curriculum and the lack of family support. The study emphasizes the need for holistic, contextual, and collaborative strategies to embed financial literacy as part of 21st-century character and life skills education.